Regional hallmarks of ethnosocial processes and interethnic relations in the Republic of Altai - Madiukova, Svetlana A.; Persidskaia, Olga A. (The New Research of Tuva, 2014)
On the basis of empirical results of sociological research in the Republic of Altai authors consider specificity of ethnosocial processes and interethnic relations in the region. Ethnosocial specificity of the region is reflected in the analysis of expert’s relations to the inflow of migrant workers and peculiarities of their interaction with the inhabitants of the Republic, to internal migration in the Republic of Altai, to the Altai as a tourism region, to the problems of  indigenous minorities of the republic. Research interest of the authors focuses on the assessment by the expert community of coherence and effectiveness of national policies in the Republic of Altai.
Keywords: interethnic relations; ethnosocial processes; national policy; regional models of national policy